Peranan DPD Dalam Sistem Ketatanegaraan RI Perspektif Sosiologis dan Hukum - Suratno, Ujang (Yustitia, 2009)
Regional Representatives Council (DPD) is a new state institution in Indonesia's state system. Regional Representatives Council was born on a national agreement to replace the position of regions an factions representatives. In socioantropologist perpective, Regional Representatives Council is intended to accomodate all kinds of local people aspiration that are not conveyed through the political parties. There for, the role of DPD should be recognized and felt by the people in their region. However, the fact shows that Regional Representatives Council is lees fuction to accomodate regional aspiration. This condition caannot be separated from to juridical aspect, Regional Representatives Council (DPD) is only assigned to porpose and discuss certain bills for certain aspect, and also to keep eyes on the implementation of the law, without being given a role to take decision.